Catalyst-free photodecarbonylation of ortho-amino benzaldehyde. Issue 11 (19th May 2020) - Zhou, Jingwei; Li, Lamei; Wang, Songping; Yan, Ming; Wei, Wentao
Abstract : Decarbonylation is easily achieved with visible light irradiation by introducing a tertiary amine into the ortho -position of the aldehyde group. Abstract : It is almost a consensus that decarbonylation of the aldehyde group (–CHO) needs to not only be mediated by transition metal catalysts, but also requires severe reaction conditions (high temperature and long reaction time). In this work, inspired by the "conformational-selectivity-based" design strategy, we broke this consensus and discovered a catalyst-free photodecarbonylation of the aldehyde group. It revealed that decarbonylation can be easily achieved with visible light irradiation by introducing a tertiary amine into the ortho -position of the aldehyde group. A diverse array of tertiary amines is tolerated by our photodecarbonylation under mild conditions. Furthermore, the (QM) computations of the mechanism and the experiments on well-designed special substrates revealed that our photodecarbonylation depends on the conformational specificity of the aldehyde group and tertiary amine, and occurs through an unusual [1, 4]-H shift and a subsequent [1, 3]-H shift.